Emergence of novel orthopox virus in Alaska, USA - Danielle Hutchinson; Mohana Kunasekaran (University of New South Wales, 2022)
Alaskapox virus was first identified following the investigation of a lesion of the shoulder of a woman from Fairbanks, Alaska, USA in July 2015 . The vesicle was swabbed, and Orthopoxvirus-generic PCR assay testing was subsequently positive . Further sequencing confirmed a novel orthopox virus, AK2015, which was later named Alaskapox virus (AKPV) . There have been three further cases in the Fairbanks area, in 2020 and 2021, each presenting with a small lesion on an extremity, and positive testing for AK2PV. Symptoms common to each case were fever, lymphadenopathy, muscle pain and fatigue, lasting between four days and six months .